[PP.22.13] IMMEDIATE POST RENAL TRANSPLANT PERIOD AND HYPERTENSION: CONCORDANCE BETWEEN CLINIC AND AMBULATORY BLOOD PRESSURE. (September 2016) - Prado, J.C.; Lopez, A.; Ruiz-Hurtado, G.; Fernandez, M.; Aguado, J.M.; Andres, A.; Praga, M.; Ruilope, L.M.; Segura, J.J.
Abstract : Objective: Our aim was to describe the degree of control of hypertension according to different clinical cut-off points and their correlation with ambulatory BP in renal transplant patients in the immediate post-transplant period. Design and method: 61 patients who had received a kidney transplant in less than 30 days are included in this analysis. Clinic BP measurement and 24-h ABPM was performed by a Mobil-O-Graph device. Standard control was defined as systolic (S)/diastolic (D) BP <140/90 mmHg and strict control as SBP/DBP <130/80 mmHg. Results: According to the standard control criteria, 49.2% of patients had controlled SBP and DBP, 14.8% had controlled only SBP, 19.7% had controlled only DBP, and 16.4% showed no control. According to strict criteria, control rates were 24.6%, 13.1%, 13.1% respectively, and 49.2% were not controlled. According to ABPM, the percentage of patients controlled in the daytime period (SBP <135 and DBP<85 mmHg) was 32.8%. The night-time control (SBP <120 and DBP <70 mmHg) was observed in 6.7%. Control within 24 hours (SBP <130 and DBP <80 mmHg) was observed in 24.6%. Comparing the strict clinical control with daytime ABPM period, we observed a concordance of 72.2% between the two techniques, with 21.3% of patients with isolated office hypertension and 6.6% of masked hypertension. When the standard clinical control was compared with daytime ABPM period, the concordance increased to 75.4%, with only 4.9% of isolated office hypertension but with an increased percentage of masked hypertension (19.7%). The agreement between both techniques peaked at 77.1% when comparing the strict clinical control with 24-hour ABPM, with 13.1% of isolated office hypertension and masked hypertension 9.8%. Conclusions: In conclusion, both clinic and ambulatory BP show a high percentage of patients with uncontrolled kidney transplant. The clinical cut-off point of 130/80 mmHg properly identify a higher percentage of patients. Uncontrolled hypertension at night-time is very prevalent. The ABPM provides additional information of great importance in the immediate post renal transplant period. Longitudinal studies with ABPM are required to assess their impact on cardiovascular prognosis in these patients.